Parasitism of Hymenoepimecis manauara Pádua & Oliveira (Hymenoptera: Ichneumonidae: Pimplinae) on Leucauge henryi Mello-Leitão (Araneae: Tetragnathidae) in Brazilian Amazonian - Pádua, Diego Galvão; Salvatierra, Lidianne; Sobczak, Jober Fernando; Oliveira, Marcio Luiz de (Biodiversity Data Journal, 2016)
Background A parasitoid wasp Hymenoepimecis manauara Pádua & Oliveira, 2015 was recorded parasitizing, for the first time, a female spider of Leucauge henryi Mello-Leitão, 1940 in the Amazon rainforest, Brazil. Images, description of the cocoon and comments about this interaction were added. New information First record of Hymenoepimecis manauara parasitizing Leucauge henryi with description of cocoon and comments about this interaction. © Pádua D et al.